Injustiça ambiental na periferia urbana: avanços e obstáculos na revitalização do Riacho das Piabas-PB - Leal, Vanda Lúcia Ouriques (2016)
This is a study of Environmental Education, management and participation. It is the analysis of a situation of degradation and, at the same time, the revitalization of the “Piabas” Stream, in Campina Grande, PB. It was felt as an environmental injustice and the main concepts that guided the study were perception, (in) environmental justice, environmental education and management, from the perspective of citizenship and participation. The general objective: to Investigate the advances and limitations of the mobilization process/inter-institutional articulation by revitalising the Piabas Stream, in Campina Grande, PB; The specific goals were defined as follows: Analyze the perception and motivation of the Community in the process of revitalization, as well as the existence of channels of access in regards to the public; Characterize the main environmental problems in the riverside communities of the Piabas Stream from the point of view of local residents; Gather information about environmental actions carried out in the area, especially those regarding the Social Environmental mobilization revitalising the Stream of Piabas. As we tried to understand the complexity of the question, we have outlined a methodological path based on bibliographic and documentary research. In addition, we used the technique of participant observation, the application of semi-structured questionnaires and a photographic record. The analysis of the data took place from categories such as satisfaction regarding the situation of pollution, the diagnosis of the situation, and desire for change, critical to the public powers that be, such as State, Legislative, Executive and Judiciary, as well as suggestions for improvement and self-criticism. The results point to the fact that there is a potential conflict, that the definition of roles and responsibilities is not yet clear for the majority, that the public power has been relatively silent, that the schools, the teachers and children are actors with potential for transformation are essential, that the Community, despite being dissatisfied, has little if mobilized and that the linkage came to formalize and to unite forces in a movement of resistance some years ago, but who needs the strength of Community willing to enter and stay in the fight and, above all, modify their way of working and relationship with the environment in which they live, because that is the only way that there will be no transformation and revitalisation of the Piabas Stream and the dignity of the population contingent.